Article RETRACTED due to manipulation by the authors Design of basic football skills test instrument for university students - Ardi Nusri; Asep Prima; Nurul Fadilah Ardi; Yovhandra Ockta; Yogi Setiawan; Bekir Erhan Orhan; Vlad Adrian Geantă; Aydin Karaçam (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Football is one of the practical courses included in the curriculum in three study programs at the Department of Sports Science, State University of Medan (Unimed). The football skills taught include short and long passing, receiving, dribbling, heading, and shooting. To date, there has not been a standardized skills test suitable for heterogeneous students, allowing lecturers to use it for assessment purposes. Therefore, it is necessary to develop a skill test so that the learning provided can be evaluated properly. It is widely recognized that assessment is a fundamental aspect of education, because inaccurate assessment can hinder the achievement of learning objectives. This study aims to identify the optimal approach to football skill test development for students. The research methodology used is the research and development (R&D) method. The research model used in this study is the Borg and Gall model which is only adopted consisting of several stages, namely needs analysis, design, development, and trial and validation. The population of the study (test takers) consisted of the male students of the Coaching Department (n=30), selected by a purposive sampling technique. The results of the analysis were analyzed using descriptive analysis and validation test analysis from expert assessments. The end result is a basic football technical test instrument, which includes instructions and drawings for each test. This test is useful for evaluating students enrolled in football courses, especially for university-level students.